Hubungan Komunikasi Terapeutik Perawat Terhadap Tingkat Kepuasan Pasien di Ruang Rawat Inap - Cut Nurliana; Solehudin Solehudin; Inas Syabanasyah (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Patient satisfaction is a key requirement for successful hospital services, influenced by factors such as mismatched expectations, nurses' personal behavior, high costs, and an unsupportive environment. Nurses' therapeutic communication plays a crucial role in increasing satisfaction in the inpatient ward by building trust and reducing misunderstandings in multicultural patients. Objective: To determine the relationship between nurses' therapeutic communication and patient satisfaction in the Inpatient Ward of Khidmat Sehat Afiat (KiSA) Regional General Hospital, Depok City in 2025. Method: A quantitative, analytical correlational study with a cross-sectional approach. The adult patient population was 120 people from August to October 2025, with a sample of 97 respondents via simple random sampling (with a 5% dropout rate). Data were collected using a questionnaire at KiSA Regional General Hospital, Depok (October-November 2025), and analyzed using chi-square for categorical variables. Results: 87.6% of nurses used good therapeutic communication; patient satisfaction was 79.3% satisfied, 27.3% quite satisfied, and 0% dissatisfied. The chi-square test yielded a p-value of 0.008 <0.05, indicating a significant relationship. Conclusion: There is a relationship between nurses' therapeutic communication and patient satisfaction levels in the Asoka Inpatient Ward of KiSA Regional General Hospital. Suggestion: Nurses should improve their skills through active listening, verbal empathy, information clarification, self-evaluation, and shift discussions for multicultural patients in Depok.